Yahya Sinwar's Murder in Arabic International Media Platforms: A Norman Fairclough Critical Discourse Analysis - Humaira, Durrotun; Basid, Abdul (Makassar State University, 2025)
Abstract. Israel’s crushing defeat in the Al-Aqsa flood incident led to Yahya Sinwar being pursued by Israel’s allies, with his death later making headlines in various international media outlets. This study aims to uncover the ideology, power, and social relations reflected in the text, discourse, and sociocultural contexts of the news coverage of Yahya Sinwar’s killing using Norman Fairclough’s critical discourse analysis. The research employs a qualitative descriptive approach. Primary data sources include news articles about Yahya Sinwar’s killing from international online media, while secondary data is drawn from books and articles relevant to the topic. The results of this study reveal that: (1) text analysis shows how Arabic-language media platforms use diction portraying Yahya Sinwar’s death as a representation of Israel’s dominance over Hamas and their ongoing relations, with Yahya Sinwar serving as the subject of the reported narratives; (2) discourse practices reveal that BBC News Arabic, France 24, and Al Jazeera, international media platforms targeting African and Middle Eastern audiences, present the discourse in distinct ways; (3) sociocultural analysis highlights that Yahya Sinwar’s killing is closely tied to the broader context of the Israel-Palestine conflict, involving various Israeli political elements and the social reactions of the Palestinian people. The findings of this study show that the narrative of Yahya Sinwar's death in various Arab media platforms has proven to have a significant social impact, namely giving rise to tensions between social groups in the Middle East and Africa regarding the Israeli-Palestinian conflict.Keywords: Critical Discourse Analysis; Hamas; Israel-Palestine; Norman Fairclough; Yahya Sinwar